IMPLEMENTATION AND PROTECTION OF LEGAL LAW ON CASH WAQF TOWARD TABUNG WAKAF INDONESIA OF DOMPET DHUAFA JAKARTA - Siti Muflichah (Jurnal Dinamika Hukum, 2017)
Waqf institution is an effort made by Muslim community and government to overcome poverty issues. One of the institutions that manage cash waqf is Wakaf Tunai Dompet Dhuafa Jakarta. Article 49 Paragraph 3 of Religious Court Law stated that the ownership of land waqf is protected and governed by the government rules This research aims to examine how the implementation and protection of waqf law on Tabung Wakaf Indonesia of Dompet Dhuafa Jakarta. This research is normative-juridical research using statute approach, conceptual approach and case approach. Then the analysis was qualitatively presented. Based on the results, the implementation of cash waqf in Tabung Wakaf Indonesia was conducted by collecting cash waqf funds to be managed into productive and non-productive activities. Tabung Wakaf Indonesia has provided legal protection to the waqif by certification of cash waqf. However, till present, there is no legitimate legality for individual cash waqf recipients or legal entities as stipulated in government regulations.Keywords: legal protection, cash waqf, tabung wakaf indonesia